Pengembangan Media Belajar Video Menggunakan Aplikasi Canva pada Materi Gerak Lurus Beraturan di Kelas XA SMA Negeri 1 Seponti - JAIS, MAD (Program Studi Pendidikan Fisika, Fakultas Pendidikan MIPA & Teknologi, Universitas PGRI Pontianak, 2023)
The development of video learning media using the Canva application, which is a learning media in uniform straight motion material, is assessed based on the assessment of material experts and media experts, as well as the feasibility of student responses to its use which is intended to determine the feasibility of the media. This study uses the ADDIE model. This model consists of the stages of analysis, design, development, implementation and evaluation, which in the study were modified into the ADD model (ie Analysis, Design, Development). In this case, the researcher used 2 media expert validators and 2 material expert validators to test the feasibility of learning video media and the suitability of the material concept. In addition, researchers observed responses to media use from 32 students at SMAN 1 Seponti which were made using a validation questionnaire. Based on the validation carried out by the material validator, video learning media using Canva achieved an average score of 82% with a very feasible category for uniform straight motion material which was validated by media experts with an average percentage of 88.75% in the category Very feasible and responsive students towards media use achieved an average score of 80.4% in the 'Good' or 'Agree' category